T.S. Eliot’s Christian Poetics and Hegel’s Ideal of Inner Sensuousness - Charles Altieri (Nordisk Poesi: Tidsskrift for Lyrikkforskning)
My essay tries to show how and why T.S. Eliot rejected Imagism as a plausible model for a truly Modern poetry—first because it could not capture the intricacy of how self-consciousness haunts all making in art by a contrast between positive assertion and all that cannot be embodied in the perceptual order. That Eliot’s Christianity then addresses this sense of shortcoming becomes important for secular possibilities of poetry because it gives him a way of aligning with Constructivist principles that emphasize the significance of our powers not just to engage objects but to manifest the powers of subjectivity in order to establish what Hegel called an “inner sensuousness”. This inner sensuousness affords the possibility of dwelling imaginatively on positive aspects of self-consciousness because art becomes an invitation to see how making affords new ways of engaging objectivity and conferring meaningfulness on experience. "Ash Wednesday” defines those powers by the kinds of awareness involved in “rejoicing to rejoice” and “striving to strive." And Murder in the Cathedral explores the logic of martyrdom in order to celebrate social relations based on faith in Incarnation that offers the possibility of love replacing the demands of the ego.